Dolley Madison saves history - Smalley, Roger; Cool, Anna Maria; Delarosa, Sam; Barnett, Charles (Mankato, Minn. : Capstone Press, 2006)
Recounts the story of how Dolley Madison became First Lady of the United States and how she saved historical items from the White House during the War of 1812.
Includes bibliographical references and index.
9 - 12 years
Keywords: Madison, Dolley -- 1768-1849; Presidents' spouses -- United States -- Juvenile literature; First ladies (United States) -- Juvenile literature; United States -- History -- War of 1812; Washington (D.C.) -- History -- Capture by the British, 1814; Juvenile literature -- Graphic books - non-fiction.